EFFECT OF MARKETING MIX ON TOURIST SATISFACTION AND LOYALTY IN TOURIST AREA OF BONO TELUK MERANTI PELALAWAN REGENCY - Lismawati Kerta Febrina; Sri Kartikowati; Jahrizal Jahrizal (JURNAL MANAJEMEN DAN BISNIS, 2021)
The study was conducted in the Bono Bay Area of ​​Meranti Bay, Pelalawan Regency. The aim is to find out the direct effect of the Marketing Mix on Tourist Satisfaction and Loyalty. This study took a sample of 145 people. The variables used are the dimensions of Marketing Mix, Tourist Satisfaction and Loyalty. Data were analyzed using SEM (Structural Equation Modeling) analysis which is operated through the SmartPLS 3.2.8 program The results showed that partially there was an effect of Product, Price, Place, Promotion, People, Process, Psychical evidence on Tourist Satisfaction. and there is the influence of tourist satisfaction on tourist loyalty. The higher the satisfaction that is owned by consumers, the loyalty of tourists is increasing.